Contextual factors as an analytical tool: Exploring collaboration and negotiation in mental health interviews in prisons mediated by non-professional interpreters - Martínez-Gómez, Aída (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article proposes a framework for analysing interpreted events mediated by non-professionals. It is based on an examination of individual contextual factors rather than on traditional definitions of setting-based features. This approach promises to be more productive for the study of non-professional interpreting and for analysing contexts that do not fit into existing categories of setting. For these purposes, this article examines a corpus of 26 prison-based mental health interviews mediated by non-professional interpreters in order to analyse the collaboration and negotiation processes that emerge among the members of the communicative triad. First, it outlines contextual factors from a conceptual perspective. Second, it describes those contextual factors that are most relevant to analysing collaboration and negotiation processes. Finally, it describes the context of prison-based mental health interviews through the lens of these factors and examines their influence on specific instances of collaboration and negotiation extracted from this corpus.